(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Rice is the most important food crop of India covering about one-fourth of the total cropped area and providing food to about half of the Indian population.This is the staple food of the people living in the eastern and the southern parts of the country, particularly in the areas having over 150 cm annual rainfall. There are about 10,000 varieties of rice in the world out of which about 4,000 are grown in India.Rice is life for thousands of millions of people. In Asia alone, more than 2,000 million people obtain 60 to 70 per cent of their calories from rice and its products. Recognizing the importance of this crop, the United Nations General Assembly declared 2004 as the “International Year of Rice” (IYR).